Yet another low‐level agent handler. (6th June 2019) - Nunnari, Fabrizio; Heloir, Alexis
Abstract: YALLAH is a framework for the creation of real‐time interactive virtual humans. Its production pipeline supports the continuous, parallel development of both the character and the software, and allows users for the deployment of a new character in a few hours of work. YALLAH is based on freely available software, mostly open‐source, and its modular software architecture provides a framework for the seamless integration of new features. Finally, thanks to transpilation, the whole framework is conceived to accommodate multiple game engines. Abstract : YALLAH is an open‐source framework for the creation of real‐time interactive virtual humans in a few hours of work. Its production pipeline supports the continuous, parallel development of both the character and the software, and its modular architecture provides a framework for the seamless integration of new features. Finally, thanks to transpilation, the whole framework is conceived to accommodate multiple game engines.